Some Immunological Evaluations of Propolis in Albino Male Mice - Ad’hiah, Ali H.; Sulaiman, Gassan M.; Al-Zaidy, Majed S. (Journal of the Faculty of Medicine Baghdad, 2007)
Propolis is a complex resinous bee product that has a wide range of biological activities. In the present investigation, two oral doses (10 and 20 mg/kg/day) of propolis (ethanol extract) were evaluated immunologically in albino male mice (80 animals) through three types of experiments. In the first, the propolis was tested alone, while in the second and third experiments, propolis was given before and after the immune suppressive drug MMC (pre- and post treatments, respectively). The three experiments were paralleled with three negative controls, in which the propolis was replaced with distilled water. In the first experiment, the dose 10 mg/kg of propolis enhanced the parameters investigated, and a significant increase was observed in the total count of leucocytes (10.7 vs. 7.8 x 103 cells/cu.mm.blood), lymphocytes (7.0 vs. 5.3 x 103 cells/cu.mm.blood), neutrophils (2.9 vs. 2.1 x 103 cells/cu.mm.blood), monocytes (0.5 vs. 0.3 x 103 cells/cu.mm.blood) and eosinophils (0.3 vs. 0.1 x 103 cells/cu.mm. blood), PI (15.2 vs. 10.8%), PFC (72 vs. 38%), AR (0.84 vs. 0.57 mm) and DTH (0.68 vs. 0.40) as compared to negative controls. Much more enhancements were observed in the dose 20 mg/kg. In the second and third experiments, a similar picture was drawn in the interaction of propolis (pre- and posttreatments) with MMC, in which the propolis extract was able to modulate the immune suppressive effect of MMC, and this was dependent on the type of treatment and dose, and again, the dose 20 mg/kg was more effective in this respect.